Les secrets dévoilés des verriers : savoirs, gestes et mesures dans les manuels techniques de verrerie du xixe siècle - Francesca Sanna (Socio-anthropologie)
At the beginning of the 19th century, the core of glassmaking craft relied on the mastery of manual transformation of materials. Throughout the century, the incorporation of new chemical and physical knowledge became essential for the production processes. However, all the socio-economic values that legitimize glassmakers’ activity still referred to a sort of “secret” of the “art”, mainly related to the unity of body and matter through the mastery of gesture. In an attempt to give a formal restitution, or a normalization of it, during 19th century technical publications like manuals aspired to measure this bodily activity in order to make it a benchmark for measuring, evaluating and teaching how to be a good glassmaker. Using a corpus of technical manuals covering the whole century, this contribution analyses this effort to unreveal the secret of glassmaking by exploring the role of the body as a element of a metrology for explaining, evaluating and teaching glassmaking technique.